PENGARUH KARAKTERISTIK INDIVIDU DAN LINGKUNGAN KERJA NON FISIK TERHADAP KINERJA KARYAWAN DI PT TIRTA INVESTAMA BANDUNG - Solihah, Indah Permata; Silvianita, Anita (2021)
Human resources are corporate assets and a very important factor to determine the success or failure of an organization in achieving its goals. Employee performance is a real behavior that everyone displays and is generated by employees. Individual characteristics are special traits that a person has that distinguishes them from others. A non-physical work environment is all circumstances that occur related to a working relationship. The purpose of this study was to find out if individual characteristics and non-physical work environment affect employee performance at PT Tirta Investama Bandung. This research uses quantitative method with descriptive research type. Sampling techniques use nonprobability sampling techniques with saturated sampling categories involving 30 respondents. Data analysis techniques use descriptive analysis and multiple linear regression analysis with the help of SPSS version 25. Based on the results of descriptive analysis of individual characteristics, non-physical work environment and overall employee performance in good category. The influence of Individual Characteristics and Non-Physical Work Environment by 44.4 and the remaining 55.6 was influenced by other variables not studied in this study. Partially, the non-physical work environment has a significant effect on employee performance and individual characteristics do not have a significant effect on employee performance at PT Tirta Investama Bandung. The highest amount of influence is the non-physical work environment and then the individual characteristics. Keywords : Individual Characteristics, Non-Physical Work Environment, Employee Performance